Regulating Political Parties European Democracies in Comparative Perspective - van Biezen, Ingrid; ten Napel, Hans-Martien (Leiden University Press, 2014)
Regulating Political Parties provides a novel and valuable contribution to the existing literature on political parties by discussing the various dimensions of party law and regulation, in Europe and other regions of the world. By bringing together international experts from the disciplines of law and political science, this volume addresses from an interdisciplinary and comparative point of view what has long been a notable lacuna in the study of political parties.